Concentrate management in desalination : case studies - Keyes, Conrad G.; Fahy, Michael P.; Tansel, Berrin (American Society of Civil Engineers, 2012)
Prepared by the Task Committee on Development of Prestandards for Concentrate Management Case Studies of the Desalination and Water Reuse Committee of the Water, Wastewater, and Stormwater Council of the Environmental and Water Resources Institute of ASCE. Concentrate Management in Desalination: Case Studies reviews the state-of-the-practice for managing concentrate streams resulting from desalination processes. Concentrate management and disposal in desalination pose environmental and cost concerns--and often determine whether a desalination project is viable, especially for inland communities. This report examines many facets of concentrate management in desalination, including process design and configuration, regulatory setting, environmental issues, and economic evaluation of projects. Twelve case studies are offered to demonstrate different techniques for disposing of concentrates associated with the following types of projects: zero liquid discharge (ZLD) and near-ZLD disposal discharge to oceans and bays deep-well injection, land application, and evaporation ponds and discharge to sanitary sewers or surface waters. Environmental engineers and managers responsible for the design, operation, research, and evaluation of regional desalination and water reuse facilities will find a wealth of practical information in this report.
Keywords: Saline water conversion -- By-products.; elektronické knihy; electronic books